A Genetic Screen for Mutants with Supersized Lipid Droplets in Caenorhabditis elegans. Issue 8 (1st August 2016) - Li, Shiwei; Xu, Shibin; Ma, Yanli; Wu, Shuang; Feng, Yu; Cui, Qingpo; Chen, Lifeng; Zhou, Shuang; Kong, Yuanyuan; Zhang, Xiaoyu; Yu, Jialei; Wu, Mengdi; et al.
Abstract: To identify genes that regulate the dynamics of lipid droplet (LD) size, we have used the genetically tractable model organism Caenorhabditis elegans, whose wild-type LD population displays a steady state of size with an upper limit of 3 μm in diameter. From a saturated forward genetic screen of 6.7 × 10 5 mutagenized haploid genomes, we isolated 118 mutants with supersized intestinal LDs often reaching 10 μm. These mutants define nine novel complementation groups, in addition to four known genes ( maoc-1, dhs-28, daf-22, and prx-10 ). The nine groups are named drop (lipid droplet abnormal) and categorized into four classes. Class I mutants drop-5 and drop-9, similar to prx-10, are up-regulated in ACS-22 -DGAT-2 -dependent LD growth, resistant to LD hydrolysis, and defective in peroxisome import. Class II mutants drop-2, drop-3, drop-6, and drop-7 are up-regulated in LD growth, are resistant to LD hydrolysis, but are not defective in peroxisome import. Class III mutants drop-1 and drop-8 are neither up-regulated in LD growth nor resistant to LD hydrolysis, but seemingly up-regulated in LD fusion. Class IV mutant drop-4 is cloned as sams-1 and, different to the other three classes, is ACS-22 -independent and hydrolysis-resistant. These four classes of supersized LD mutants should be valuable for mechanistic studies of LD cellular processes including growth, hydrolysis, and fusion.